2016
DOI: 10.3349/ymj.2016.57.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Darapladib, a Lipoprotein-Associated Phospholipase A2 Inhibitor, Reduces Rho Kinase Activity in Atherosclerosis

Abstract: PurposeIncreased lipoprotein-associated phospholipase A2 (Lp-PLA2) activity and Rho kinase activity may be associated with atherosclerosis. The principal aim of this study was to examine whether darapladib (a selective Lp-PLA2 inhibitor) could reduce the elevated Lp-PLA2 and Rho kinase activity in atherosclerosis.Materials and MethodsStudies were performed in male Sprague-Dawley rats. The atherosclerosis rats were prepared by feeding them with a high-cholesterol diet for 10 weeks. Low-dose darapladib (25 mg·kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…5) is a potent and selective inhibitor of LpPLA 2 (IC 50 0.25 nM against recombinant human LpPLA 2 in a DNPG assay), developed by GlaxoSmithKline [111], that has undergone two phase 3 trials for cardiovascular disease, but has been discontinued because of failure to reduce the risk of major coronary events [112,113]. Recently, darapladib was found to reduce elevated LpPLA 2 , Rho kinase activity, and cardiomyocyte apoptosis in atherosclerosis, which can lead to cardiovascular protection [114]. In an in vivo rat type 2 diabetes mellitus model, darapladib was proven to reduce inflammation [115], to decrease vascular cell adhesion molecule-1 and intercellular adhesion molecules-1 aorta expression in early stages of atherosclerosis [116] and to improve insulin resistance occurring in the metabolic disorder [117].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…5) is a potent and selective inhibitor of LpPLA 2 (IC 50 0.25 nM against recombinant human LpPLA 2 in a DNPG assay), developed by GlaxoSmithKline [111], that has undergone two phase 3 trials for cardiovascular disease, but has been discontinued because of failure to reduce the risk of major coronary events [112,113]. Recently, darapladib was found to reduce elevated LpPLA 2 , Rho kinase activity, and cardiomyocyte apoptosis in atherosclerosis, which can lead to cardiovascular protection [114]. In an in vivo rat type 2 diabetes mellitus model, darapladib was proven to reduce inflammation [115], to decrease vascular cell adhesion molecule-1 and intercellular adhesion molecules-1 aorta expression in early stages of atherosclerosis [116] and to improve insulin resistance occurring in the metabolic disorder [117].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…Emerging therapeutic approaches targeting rHDL have been investigated to reduce the risk of cardiovascular events in the past decades [52,53]. One of the important therapies is apoAI Milano (apoA-IM), a naturally occurring mutant of apoAI that was shown to be related with cardioprotective effects [54].…”
Section: Reconstituted Apoai Milano/palmitoyl-oleoyl Phosphatidyl Chomentioning
confidence: 99%
“…The ubiquitously expressed Rho-kinase, which is a serine/threonine kinase, has been reported to serve an important role in a number of major cardiovascular diseases, such as hypertension, heart failure, pulmonary hypertension, atherosclerosis, myocardial infarction and myocardial I/R (5)(6)(7)(8)(9)(10)(11). Previous studies have demonstrated that Rho-kinase activation is involved in the pathogenesis of I/R in vivo (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%